Synthesis method and application of monoclinic system hafnium oxide nanorod
By using micron-sized hafnium dioxide powder crystals and potassium hydrofluoride, and using a two-step method of high-temperature roasting and hydrolysis, monoclinic hafnium dioxide nanorods were successfully synthesized and used in coatings, solving the complexity and cost of the existing process. High problem, achieving uniform particle size and efficient coating effect.
Patent Information
- Application Number
- CN202411385924.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing nanohafnium dioxide preparation process is complex, has high cost, and the products are prone to agglomeration, making it difficult to obtain nano-short rods of uniform particle size.
Micron-sized hafnium dioxide powder crystals and potassium hydrofluoride are used as raw materials, and monoclinic hafnium dioxide nanorods are synthesized through a two-step method of high-temperature roasting and subsequent hydrolysis. This method uses only four common inorganic reagents, simplifying the process and reducing costs.
Monoclinic hafnium dioxide nanorods with uniform particles and basically no agglomeration were successfully obtained, and showed good performance in coating on plastic or metal surfaces.
Smart Images

Figure HDA0005070978750000011 
Figure HDA0005070978750000012 
Figure HDA0005070978750000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano multifunctional materials, and specifically relates to a synthesis method and application of monoclinic hafnium dioxide (HfO2) nanorods, and in particular to a synthesis method of monoclinic hafnium dioxide short nanorods with uniform particle size and the application of the hafnium dioxide short nanorods in plastic or metal surface coating. Background Art
[0002] Nanomaterials have unique physical and chemical properties that are different from those of mesoscopic and microscopic materials, and have broad application prospects in the fields of chemistry, biology, environment, optics, electronics, information, and new energy. With the rapid development of nanoscience and nanomaterial research in the past decade, nanomaterials with various morphological characteristics and corresponding functions have been discovered one after another, which has further promoted the synthesis, preparation, and development of new nanomaterials with more morphological characteristics.
[0003] Hafnium dioxide (HfO2) is a very important structural and functional material with excellent physical and chemical properties, such as high melting point (about 2900℃), high hardness, wide band gap, high dielectric constant, good thermal stability and chemical stability, excellent resistance to laser damage, good transparency in the ultraviolet to infrared band, high refractive index and low extinction coefficient, etc. Therefore, hafnium dioxide is widely used in optical films, high-performance devices, high-energy lasers, fast ion conductor fuel cells, oxygen sensors, refractory materials, oxygen insulation material coatings, control rods of atomic reactors, etc., and is also expected to be used in automobile exhaust and atmospheric environment monitoring, fuel cells, metallurgy and other broader fields. In addition, hafnium dioxide dielectric materials have a simple cubic crystal structure and a wide band gap, high k value, large conduction band offset and step band cheapness to silicon, as well as good thermodynamic stability and good lattice matching with silicon. It is currently one of the most promising new high-k gate dielectric materials to replace silicon dioxide and is receiving increasing attention.
[0004] Compared with other nano-oxide functional materials, the preparation and synthesis methods of nano-hafnium dioxide are relatively rare, which can be summarized as hydrothermal method, chemical vapor deposition method, sol-gel method and physical vapor deposition method.
[0005] In the above-mentioned synthesis process, multiple reagents such as hafnium raw materials + precipitant ± stabilizer ± solvent are used. The hafnium raw materials currently used include hexahydrate hafnium dichloride (HfCl2·6H2O), tetrahydrate hafnium sulfate (Hf(SO4)2·4H2O), octahydrate hafnium oxychloride (HfOCl2·8H2O), hafnium chloride (HfCl4), isobutoxy hafnium and metal Hf and / or hafnium dioxide, and some inorganic or organic reagents are used as auxiliary reagents (such as hydrochloric acid, borax, polyethylene glycol, ethanol, octadecyltrichlorosilane, acetone, toluene, etc.). Therefore, in the existing process for synthesizing nano hafnium dioxide, the types of hafnium source raw materials used are relatively single, and the products are very easy to agglomerate. It is necessary to further develop new high-quality and low-cost hafnium source raw materials and obtain better quality products. At the same time, a variety of inorganic and organic reagents are used in the existing process, some of which are relatively rare and expensive, which increases the synthesis cost and makes the synthesis process too complicated. It is also urgent to simplify the synthesis process to reduce the synthesis cost. Summary of the invention
[0006] The present invention aims to provide a method for synthesizing monoclinic hafnium dioxide nanorods. The method uses micron-sized hafnium dioxide powder crystals and potassium bifluoride as raw materials, and synthesizes monoclinic hafnium dioxide nanorods through a two-step method of high-temperature roasting and subsequent hydrolysis. The monoclinic hafnium dioxide nanorods have uniform particles and are basically free of agglomeration.
[0007] The present invention also aims to provide the use of the monoclinic hafnium dioxide nanorods synthesized by the above method in plastic or metal surface coating.
[0008] The first object of the present invention can be achieved by the following technical solution: A method for synthesizing monoclinic hafnium dioxide nanorods, comprising the following steps:
[0009] (1) Using hafnium dioxide and potassium bifluoride powder as initial raw materials, the two raw materials are placed in a container and covered, and the container is heated to a temperature of 350 to 400° C. for a heating time of 0.25 to 1 hour to allow the solid powder to undergo a sufficient melting reaction, and then cooled after the reaction, a dilute hydrofluoric acid solution is added to the container, and the container is heated to boiling again, and the container is continuously stirred to completely dissolve the solid in the container, and the heating is stopped;
[0010] (2) filtering the solution in the container while hot and collecting the filtrate;
[0011] (3) diluting the filtrate obtained in step (2) with deionized water to obtain a dilute solution, placing the dilute solution in a hydrothermal reaction container, sealing the hydrothermal reaction container, heating the hydrothermal reaction container, adjusting the temperature in the hydrothermal reaction container to 150-500° C., adjusting the pressure in the hydrothermal reaction container to 10-100 MPa by injecting inert gas into the hydrothermal reaction container, reacting for 10-15 hours, and rapidly cooling to room temperature after the reaction;
[0012] (4) Opening the hydrothermal reaction vessel, and obtaining monoclinic hafnium dioxide nanorods through subsequent treatment.
[0013] The present invention uses micron-sized hafnium dioxide powder crystals and potassium bifluoride as raw materials, and synthesizes monoclinic hafnium dioxide nanorods with uniform particle size through a two-step method of high-temperature roasting and subsequent hydrolysis. The entire process only uses four inorganic reagents, hafnium dioxide, potassium bifluoride, hydrofluoric acid and ethanol. The synthetic raw materials are common, simple and easy to obtain, the reaction time is extremely short, the reaction temperature is low, and complex processes are avoided, and the process is simplified; the synthesized monoclinic hafnium dioxide nanorods have uniform particles and are basically free of agglomeration.
[0014] In the above-mentioned method for synthesizing monoclinic hafnium dioxide nanorods:
[0015] Optionally, the mass ratio of hafnium dioxide to potassium bifluoride in step (1) is 1:2-3.
[0016] Optionally, the volume percentage of the dilute hydrofluoric acid solution in step (1) is 3-8%, preferably 5%, and the amount added is 40-60%, preferably 50% of the total volume of the container.
[0017] Optionally, the container in step (1) is a crucible, and the crucible is a nickel-based alloy crucible or a precious metal crucible.
[0018] Optionally, a Teflon stirring rod is used for stirring in step (1).
[0019] More preferably, in step (1), the container is heated at a temperature of 350° C. and a heating time of 0.5 hours.
[0020] Optionally, in step (2), a silver evaporating dish or an evaporating dish with a Teflon lining is used to collect the filtrate.
[0021] Optionally, the molar concentration of the dilute solution in step (3) is 0.01 to 0.02 mol / L.
[0022] More preferably, the reaction temperature in step (3) is 250-350°C.
[0023] Optionally, the inert gas in step (3) is argon or helium.
[0024] Optionally, the reaction time described in step (3) includes the time consumed for heating.
[0025] Optionally, the rapid cooling in step (3) is to use ice water or compressed air to quickly cool the hydrothermal reaction container.
[0026] As one of the preferred technical solutions of the present invention, in step (3), the dilute solution is directly added to the hydrothermal reaction vessel, and the volume of the dilute solution accounts for 30-80% of the total volume of the hydrothermal reaction vessel; the hydrothermal reaction vessel is a hydrothermal reaction kettle, and the hydrothermal reaction kettle is a sealed high-temperature and high-pressure reaction kettle, and the high-temperature and high-pressure reaction kettle is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reaction kettle has a metal shell, and the metal shell is provided with a strong acid and strong alkali resistant lining, and the strong acid and strong alkali resistant lining is polytetrafluoroethylene, polyphenyl ester, polyimide plastic, or the strong acid and strong alkali resistant lining is silver, gold or platinum inert metal, or the strong acid and strong alkali resistant lining is gold palladium or silver palladium alloy.
[0027] Optionally, the hydrothermal reactor is a conventional hydrothermal reactor, the sealed high-temperature and high-pressure reactor is a conventional sealed high-temperature and high-pressure reactor, and the metal shell is conventional stainless steel or Hastelloy.
[0028] When adopting this technical solution, optionally, in step (4), the hydrothermal reaction container is opened, and the monoclinic hafnium dioxide nanorods are obtained through subsequent treatment, including: opening the hydrothermal reaction container, recovering the residual solution in the hydrothermal reaction container, washing the inner wall of the hydrothermal reaction container with deionized water, collecting the washed fluid to obtain nano hafnium dioxide turbid liquid, centrifuging the obtained turbid liquid, removing the lower layer of precipitate, washing and drying the lower layer of precipitate to obtain monoclinic hafnium dioxide nanorods with uniform particle size.
[0029] When adopting this technical solution, optionally, a sample collection sheet is provided at the bottom of the hydrothermal reaction container in step (3), and the sample collection sheet is a sample collection sheet made of plastic or inert metal; in step (4), the hydrothermal reaction container is opened, and monoclinic hafnium dioxide nanorods are obtained through subsequent treatment, including: opening the hydrothermal reaction container, recovering the residual solution in the hydrothermal reaction container, taking out the sample collection sheet, washing and drying, and obtaining monoclinic hafnium dioxide nanorods with uniform particle size on the surface of the sample collection sheet.
[0030] Optionally, the plastic is polytetrafluoroethylene, polyphenylene ester, polyimide, etc., and the inert metal material is silver, gold or platinum, etc.
[0031] Optionally, the cleaning or washing is performed by washing with deionized water and anhydrous ethanol 2 to 3 times in sequence.
[0032] Optionally, the drying is natural air drying or storage in a desiccating dish.
[0033] Therefore, in order to directly perform nano hafnium dioxide coating on plastic or metal, the plastic or inert metal can also be placed at the bottom of the hydrothermal reaction vessel in step (3) of the present invention.
[0034] As another preferred technical solution of the present invention, in step (3), the dilute solution is first added to a precious metal vessel, and then the precious metal vessel is placed in a hydrothermal reaction vessel, the precious metal is silver, gold or platinum; or the precious metal is gold-palladium or silver-palladium alloy; the high-temperature and high-pressure reactor is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reactor has a metal shell.
[0035] When adopting this technical solution, optionally, in step (4), the hydrothermal reaction vessel is opened, and the monoclinic hafnium dioxide nanorods are obtained through subsequent treatment, including: opening the hydrothermal reactor, taking out the precious metal container, recovering the residual solution in the precious metal container, washing the inner wall of the precious metal container with deionized water, collecting the washed fluid to obtain nano hafnium dioxide turbid liquid, centrifuging the obtained turbid liquid, taking the lower layer of precipitate, washing and drying the lower layer of precipitate to obtain monoclinic hafnium dioxide nanorods.
[0036] Optionally, the cleaning is performed by washing with deionized water and anhydrous ethanol 2 to 3 times in sequence.
[0037] Optionally, the drying is natural air drying or storage in a desiccating dish.
[0038] Optionally, the residual solution mainly comprises potassium hafnium hexafluoroate, hydrofluoric acid and potassium fluoride.
[0039] The first object of the present invention can be achieved by the following technical solution: application of the monoclinic hafnium dioxide nanorods synthesized by the above method in coating of plastic or metal surface.
[0040] The plastics include organic plastics such as polytetrafluoroethylene, polyphenylene ester, polyimide, etc., and the metals include common stainless steel, nickel-based alloys, molybdenum-based alloys, gold, silver, copper, platinum, etc.
[0041] The core of the method for preparing hafnium dioxide nanorods of the present invention is to synthesize potassium hafnium hexafluoroate by using hafnium dioxide and potassium bifluoride at high temperature, and then generate nano hafnium dioxide crystals by the hydrolysis reaction of potassium hafnium hexafluoroate. By controlling the temperature, pressure and fluorine fugacity, monoclinic hafnium dioxide short rod-shaped nanocrystals with uniform particle size are regulated.
[0042] Using the relatively cheap nano hafnium dioxide powder crystals commonly found on the market as the hafnium source, hafnium dioxide and potassium bifluoride are first melted at high temperature to undergo the following reaction:
[0043] HfO2+4KHF2→K2HfF6+2HF↑+2H2O↑
[0044] The final products of the reaction are potassium hafnium hexafluoroate and excess potassium bifluoride, which are redissolved by adding a dilute hydrofluoric acid solution, and then separated from potassium bifluoride by repeated filtration and recrystallization, thereby obtaining a high-purity potassium hafnium hexafluoroate filtrate.
[0045] Then, deionized water is added to the potassium hafnium hexafluoroate filtrate to prepare a potassium hafnium hexafluoroate dilute solution, and the potassium hafnium hexafluoroate dilute solution is placed in a hydrothermal reactor, and the hydrothermal reactor is heated and pressurized. Under the hydrothermal conditions, potassium hafnium hexafluoroate and water undergo the following hydrolysis reaction:
[0046] K2HfF6+2H2O→HfO2↓+4HF+2KF
[0047] After the reaction is completed, the hydrothermal reactor is quickly cooled to room temperature, and the obtained precipitate is washed and dried to obtain a monoclinic hafnium dioxide nanorod sample.
[0048] In the method for preparing short hafnium dioxide nanorods of the present invention, the core reagents used are hafnium dioxide and potassium bifluoride, thereby avoiding the complicated process of using multiple raw materials such as hafnium source + precipitant + stabilizer + solvent in the existing process. Potassium hexafluorohafnate synthesized by melting hafnium dioxide and potassium bifluoride is hydrolyzed to generate hafnium dioxide nanocrystals and hydrogen fluoride. Fluorine ions generated by ionization of hydrogen fluoride are adsorbed on the surfaces (111) and (200) of the hafnium dioxide nanocrystals, reducing the surface energy of the surfaces (111) and (200) of the hafnium dioxide nanocrystals and promoting the growth of the surfaces (111) and (200); at the same time, hydrogen fluoride dissolves the development of other crystal faces of the hafnium dioxide crystals, thereby finally synthesizing rod-shaped hafnium dioxide crystals with developed surfaces (111) and (200) and weakly developed other crystal faces. Since the potassium hafnium hexafluoroate hydrolysis reaction in step (3) of the present invention is an incomplete reaction, the recovery solution in step (4) of the present invention mainly comprises potassium hafnium hexafluoroate, potassium fluoride and hydrogen fluoride. A certain amount of hafnium dioxide powder is added to the recovery solution. The obtained recovery solution can continue to be used as the initial raw material of the present invention. On the one hand, it can effectively recover and reduce costs, and on the other hand, it can eliminate hydrofluoric acid pollution and maintain process safety.
[0049] Compared with the prior art, the synthesis method of the present invention has the following beneficial effects:
[0050] (1) The synthesis method of the present invention uses common and inexpensive nano hafnium dioxide powder and potassium bifluoride reagents to synthesize potassium hexafluorohafnium oxide by high-temperature calcination of the two initial reagents, and generates short rod-shaped hafnium dioxide nanocrystals by the hydrolysis reaction of potassium hexafluorohafnium oxide under hydrothermal conditions, thereby realizing the preparation of hafnium dioxide nanocrystals with specific morphology using simple common reagents, expanding and enriching the preparation process of hafnium dioxide nanomaterials;
[0051] (2) The synthesis method of the present invention only requires the use of four common and inexpensive reagent raw materials, namely hafnium dioxide, potassium bifluoride, hydrofluoric acid and ethanol, thereby avoiding the use of a variety of expensive precursors, precipitants, stabilizers, solvents and other morphology control agents, as well as the sequential process steps in the traditional process. Therefore, the method is simple in process, easy to operate and control, and relatively low in cost;
[0052] (3) The recovered solution obtained by the synthesis method of the present invention mainly comprises potassium hafnium hexafluoroate, potassium fluoride and hydrogen fluoride. Hafnium dioxide powder is added to the recovered solution for reprocessing, and potassium fluoride and hydrofluoric acid can be further synthesized into potassium hafnium hexafluoroate. Therefore, the recovered solution obtained can be further used as the initial raw material of the present invention. On the one hand, it can effectively recover and reduce costs, and on the other hand, it can eliminate hydrofluoric acid pollution and maintain process safety.
[0053] (4) The synthesis method of the present invention uses common and inexpensive hafnium dioxide and potassium bifluoride reagents to synthesize pure potassium hafnium hexafluoroate crystals through two initial reagents. Potassium hafnium hexafluoroate can continue to be used as an intermediate product for preparing hafnium dioxide nanorods, and can also be used as an additional chemical product. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 is the XRD powder diffraction pattern of the filtrate condensate in Example 1 of the present invention, and the arrow represents the main diffraction peak of potassium hexafluorohafnium oxide;
[0055] Figure 2 The photomicrographs (a) to (b) and scanning electron microscope photos (c) to (d) of the hafnium dioxide nanorod coating prepared in Example 1 of the present invention at different magnifications are shown, wherein (a) is magnified 50 times, (b) is magnified 400 times, (c) is magnified 20,000 times, and (d) is magnified 50,000 times;
[0056] Figure 3 The scanning electron microscope photographs (a) to (d) of the hafnium dioxide nanorod sample prepared in Example 2 of the present invention at different magnifications, wherein (a) is magnified 15,000 times, (b) is magnified 12,000 times, (c) is magnified 40,000 times, and (d) is magnified 6,000 times;
[0057] Figure 4 The scanning electron microscope photographs (a) to (d) of the hafnium dioxide nanorod sample prepared in Example 3 of the present invention at different magnifications, wherein (a) is magnified 4,000 times, (b) is magnified 10,000 times, (c) is magnified 15,000 times, and (d) is magnified 30,000 times;
[0058] Figure 5The scanning electron microscope photographs (a) to (d) of the hafnium dioxide nanorod sample prepared in Example 4 of the present invention at different magnifications, wherein (a) is magnified 10,000 times, (b) is magnified 10,000 times, (c) is magnified 15,000 times, and (d) is magnified 40,000 times;
[0059] Figure 6 The photomicrographs (a) to (b) and scanning electron microscope photos (c) to (d) of the hafnium dioxide nanorod coating prepared in Example 5 of the present invention at different magnifications are shown, wherein (a) is magnified 50 times, (b) is magnified 400 times, (c) is magnified 4,000 times, and (d) is magnified 15,000 times;
[0060] Figure 7 The photomicrographs (a) to (b) and scanning electron microscope photos (c) to (d) of the hafnium dioxide nanorod coating prepared in Example 6 of the present invention at different magnifications are shown, wherein (a) is magnified 50 times, (b) is magnified 400 times, (c) is magnified 4,000 times, and (d) is magnified 6,000 times;
[0061] Figure 8 The scanning electron microscope photographs (a) to (d) of the hafnium dioxide nanorod sample prepared in Example 7 of the present invention at different magnifications, wherein (a) is magnified 2,500 times, (b) is magnified 6,000 times, (c) is magnified 10,000 times, and (d) is magnified 20,000 times;
[0062] Fig. 9 The laser Raman spectra of the hafnium dioxide nanorod samples and the standard hafnium dioxide powder under different conditions are compared;
[0063] Fig.10 The μ-XRD powder diffraction patterns of the hafnium dioxide nanorod samples under different conditions of the present invention, wherein (1) is the result of the monoclinic hafnium dioxide nanorod sample synthesized in Example 1 of the present invention; (2) is the result of the monoclinic hafnium dioxide nanorod sample synthesized in Example 2 of the present invention; (3) is the result of the monoclinic hafnium dioxide nanorod sample synthesized in Example 3 of the present invention; (4) is the result of the monoclinic hafnium dioxide nanorod sample synthesized in Example 4 of the present invention; (5) is the result of the monoclinic hafnium dioxide nanorod sample synthesized in Example 5 of the present invention; (6) is the result of the monoclinic hafnium dioxide nanorod sample synthesized in Example 6 of the present invention, wherein the ordinate Intensity (Counts) is the count, and the abscissa Two-Theta (deg) is the diffraction angle. DETAILED DESCRIPTION
[0064] The present invention is further described below in conjunction with specific examples. The following examples are only for illustrative purposes and are not to be construed as limiting the present invention. Unless otherwise specified, the raw materials used in the following examples are conventional commercially available or commercially available raw materials, and unless otherwise specified, the methods and equipment used in the following examples are conventional methods and equipment used in the art.
[0065] The present invention is further described below in conjunction with examples and drawings, but the scope of protection claimed by the present invention, such as the reaction device, reaction temperature, reaction time and volume of the reaction liquid, is not limited to those in the examples.
[0066] Example 1
[0067] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0068] (1) 0.51 g of hafnium dioxide (HfO2, 99.99% purity, micron-sized powder crystal, Aladdin, the same below) and 1.02 g of potassium hydrogen fluoride (KHF, 99% purity, Aladdin, the same below) powder are placed in a silver crucible, the lid is closed, the silver crucible is placed on an electric furnace, the temperature of the electric furnace is set to 350° C., and the crucible is heated for half an hour to allow the solid powder to undergo a full melting reaction. After cooling slightly, the crucible lid is opened, and hydrofluoric acid with a volume percentage of 5% is added to the crucible until it reaches half the volume of the crucible. The electric furnace is continued to be turned on to heat until boiling, and a Teflon rod is used to stir continuously to completely dissolve the solid in the crucible, and the heating is stopped;
[0069] (2) Pour the solution in the crucible onto filter paper while it is still hot and filter it. Use a silver evaporating dish to collect the filtrate. Repeat the filtration three times to obtain the filtrate. After the filtrate is condensed, rod-shaped powder crystals can be obtained. Figure 1 XRD analysis confirmed that it was potassium hexafluorohafnium oxide crystals;
[0070] (3) diluting the filtrate obtained in step (2) with deionized water to obtain a 0.01 mol / L reaction solution, and charging the obtained reaction solution into a 200 mL hydrothermal reactor. The hydrothermal reactor is a sealed high-temperature and high-pressure reactor commonly found in the market. The high-temperature and high-pressure reactor is connected with a high-precision ultra-high-pressure pressure gauge, a ventilation pipe, and an air inlet and an air outlet stop valve. The high-temperature and high-pressure reactor has a stainless steel or Hastelloy metal shell. A flat gold sheet is placed at the bottom of the reactor. After tightening the reactor, close the air outlet stop valve, open the air inlet stop valve, inject argon into the reactor through the ventilation pipe to a pressure of 80 MPa, close the air inlet stop valve to stop gas injection, heat the reactor with a heating furnace, and set the reaction temperature to 250° C. After the temperature rises to 250° C., open the air inlet stop valve in step (3), continue to supplement the injection of argon to a pressure of 100 MPa, and maintain the reaction time for 12 hours. After the reaction is completed, use ice water to pour the reactor in step (3) to quickly cool it to room temperature.
[0071] (4) Open the stop valve of the air outlet of the reactor in step (3) to release the pressure, then open the reactor, recover the residual solution in the reactor, take out the gold flakes in the reactor in step (3), wash them with deionized water for 2 to 3 times, and after natural air drying, a layer of hafnium dioxide coating can be seen on the surface of the gold flakes.
[0072] Figure 2 Figures (a) and (b) are micrographs of the coating layer at different magnifications; Figure 2 Figures (c) to (d) are scanning electron microscope photos of hafnium dioxide at different magnifications. The morphology shows that these hafnium dioxide nanocrystals are short columnar, with a particle size of tens of nanometers to 300 nanometers, and are dispersed.
[0073] Fig. 9 The laser Raman spectrum analysis in the experiment showed that although there was obvious fluorescence interference in the low-wavelength band, the laser Raman peak intensity of the nanocrystals synthesized at 250°C was relatively obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm -1 、258cm -1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1 , indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0074] Fig.10The XRD powder diffraction analysis in the results shows that the hafnium dioxide crystals are monoclinic and have developed multiple crystal planes such as (111), (200), (020), (022), and (300).
[0075] Example 2
[0076] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0077] (1) The filtrate obtained in step (2) of Example 1 was diluted with deionized water to obtain a 0.01 mol / L reaction solution. 5 mL of the prepared reaction solution was placed in a gold tube with a diameter of 4.5 mm and then welded and sealed. The gold tube was then placed in a high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected to a high-precision ultra-high pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor had a stainless steel or Hastelloy metal shell. After the reactor was tightened, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa. The stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 300° C. After the temperature rose to 300° C., the stop valve was opened and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 10 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.
[0078] (2) The reaction kettle in step (1) is opened, the gold tube is taken out and broken, the residual solution in the precious metal container is recovered, and the inner wall of the gold tube is washed with deionized water. The washed fluid is collected to obtain a nano hafnium dioxide turbid liquid, and the obtained turbid liquid is placed in a centrifuge for centrifugation. After the centrifugation, the lower layer of precipitate is taken out and rinsed with deionized water for 2 to 3 times. Finally, the precipitate is naturally air-dried to obtain monoclinic hafnium dioxide nanorods with uniform particle size.
[0079] Figure 3 The middle figures (a) to (d) show the morphology and particle size of hafnium dioxide nanorods at different magnifications, with the particle size ranging from tens of nanometers to 400 nanometers.
[0080] Fig. 9 The laser Raman spectrum analysis in the experiment showed that although there was obvious fluorescence interference in the low-wavelength band, the laser Raman peak intensity of the nanocrystals synthesized at 300°C was relatively obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm -1 、258cm -1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1, indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0081] Fig.10 The XRD powder diffraction analysis in the results shows that the hafnium dioxide crystals are monoclinic and have developed multiple crystal planes such as (111), (200), (020), (022), and (300).
[0082] Example 3
[0083] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0084] (1) The filtrate obtained in step (2) of Example 1 was diluted with deionized water to obtain a 0.01 mol / L reaction solution, and the obtained reaction solution was placed in a 200 mL hydrothermal reactor. The hydrothermal reactor was a sealed high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected with a high-precision ultra-high pressure pressure gauge, a ventilation pipe, and an air inlet and an air outlet stop valve. The high-temperature and high-pressure reactor had a stainless steel or Hastelloy metal shell, and a silver lining was provided in the metal shell. A flat gold sheet was placed at the bottom of the reactor. After the reactor was tightened, the air outlet stop valve was closed, the air inlet stop valve was opened, argon was injected into the reactor through the ventilation pipe to a pressure of 50 MPa, the air inlet stop valve was closed to stop the gas injection, and the reactor was heated by a heating furnace, and the reaction temperature was set to 400° C. After the temperature rose to 400° C., the air inlet stop valve was opened, and argon was continuously injected to a pressure of 80 MPa. The reaction time was maintained for 15 hours. After the reaction was completed, ice water was used to quickly cool the reactor to room temperature.
[0085] (2) Open the stop valve of the gas outlet of the reactor in step (1) to release the pressure, then open the reactor, recover the residual solution in the reactor, take out the gold flakes in the reactor, wash them with deionized water for 2 to 3 times, and after natural air drying, a layer of hafnium dioxide coating can be seen on the surface of the gold flakes.
[0086] Figure 4 The middle (a) scanning electron microscope photo shows the hafnium dioxide nanofilm; Figure 4 Figures (b) to (d) are scanning electron microscope photos of hafnium dioxide at different magnifications. The morphology shows that these hafnium dioxides are relatively self-shaped short rods with a particle size of 100 nanometers to 500 nanometers.
[0087] Fig. 9 The laser Raman spectrum analysis in the experiment showed that although there was obvious fluorescence interference in the low-wavelength band, the laser Raman peak intensity of the nanocrystals synthesized at 400°C was relatively obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm -1 、258cm-1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1 , indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0088] Fig.10 The XRD powder diffraction analysis in the results shows that the hafnium dioxide crystals are monoclinic and have developed multiple crystal planes such as (111), (200), (020), (022), and (300).
[0089] Example 4
[0090] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0091] (1) The filtrate obtained in step (2) of Example 1 was diluted with deionized water to obtain a 0.01 mol / L reaction solution. 5 mL of the prepared reaction solution was placed in a gold tube with a diameter of 4.5 mm and then welded and sealed. The gold tube was then placed in a high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected to a high-precision ultra-high pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor had a stainless steel or Hastelloy metal shell. After the reactor was tightened, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa. The stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 500° C. After the temperature rose to 500° C., the middle stop valve was opened, and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 12 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.
[0092] (2) The reaction kettle in step (1) is opened, the gold tube is taken out and broken open, and the inner wall of the gold tube is washed with deionized water. The washed fluid is collected to obtain a nano-hafnium dioxide turbid liquid, and the obtained turbid liquid is placed in a centrifuge for centrifugation. After the centrifugation, the lower layer of precipitate is taken out and rinsed with deionized water for 2 to 3 times, and finally the precipitate is naturally air-dried to obtain hafnium dioxide nanorods.
[0093] Figure 5 Figures (a) to (d) show the morphology and particle size of hafnium dioxide nanorods at different magnifications, with particle sizes ranging from 100 nanometers to 500 nanometers.
[0094] Fig. 9 The laser Raman spectroscopy analysis in the experiment showed that the laser Raman peak of the nanocrystals synthesized at 500°C was obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm-1 、258cm -1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1 , indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0095] Fig.10 The XRD powder diffraction analysis in the results shows that the hafnium dioxide crystals are monoclinic and have developed multiple crystal planes such as (111), (200), (020), (022), and (300).
[0096] Example 5
[0097] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0098] (1) The filtrate obtained in step (2) of Example 1 was diluted with deionized water to obtain a 0.02 mol / L reaction solution, and the obtained reaction solution was placed in a 200 mL hydrothermal reactor. The hydrothermal reactor was a sealed high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected with a high-precision ultra-high pressure pressure gauge, a ventilation pipe, and an air inlet and an air outlet stop valve. The high-temperature and high-pressure reactor had a stainless steel or Hastelloy metal shell, and a silver lining was provided in the metal shell. A flat gold sheet was placed at the bottom of the reactor. After the reactor was tightened, the air outlet stop valve was closed, the air inlet stop valve was opened, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa, the air inlet stop valve was closed to stop the gas injection, and the reactor was heated by a heating furnace, and the reaction temperature was set to 300° C. After the temperature rose to 300° C., the air inlet stop valve was opened, and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 12 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.
[0099] (2) Open the stop valve of the gas outlet of the reactor in step (1) to release the pressure, then open the reactor, recover the residual solution in the reactor, take out the gold flakes in the reactor in step (1), wash them with deionized water for 2 to 3 times, and after natural air drying, a layer of hafnium dioxide coating can be seen on the surface of the gold flakes. Figure 5 (a) and (b) Scanning electron micrographs show the hafnium dioxide nanofilm.
[0100] Figure 6 Figures (a) and (b) are microscopic photographs of the coating layer at different magnifications, and Figures (c) to (d) are scanning electron microscope photographs of hafnium dioxide at different magnifications. The morphology shows that these hafnium dioxide are relatively self-shaped short rods with a particle size of 200 nanometers to 800 nanometers.
[0101] Fig. 9 The laser Raman spectroscopy analysis in the experiment showed that the laser Raman peak of the nanocrystals synthesized at 300°C was obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm -1 、258cm -1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1 , indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0102] Fig.10 The XRD powder diffraction analysis in the results shows that the hafnium dioxide crystals are monoclinic and have developed multiple crystal planes such as (111), (200), (020), (022), and (300).
[0103] Example 6
[0104] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0105] (1) The filtrate obtained in step (2) of Example 1 was diluted with deionized water to obtain a 0.02 mol / L reaction solution, and the obtained reaction solution was placed in a 200 mL hydrothermal reactor. The hydrothermal reactor was a sealed high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected with a high-precision ultra-high pressure gauge, a ventilation pipe, and an air inlet and an air outlet stop valve. The high-temperature and high-pressure reactor had a stainless steel or Hastelloy metal shell, and a silver lining was provided in the metal shell. A flat gold sheet was placed at the bottom of the reactor. After the reactor was tightened, the air outlet stop valve was closed, the air inlet stop valve was opened, argon was injected into the reactor through the ventilation pipe to a pressure of 60 MPa, the air inlet stop valve was closed to stop the gas injection, and the reactor was heated by a heating furnace, and the reaction temperature was set to 400° C. After the temperature rose to 400° C., the air inlet stop valve was opened, and argon was continuously injected to a pressure of 80 MPa. The reaction time was maintained for 15 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.
[0106] (2) Open the stop valve of the gas outlet of the reactor in step (1) to release the pressure, then open the reactor, recover the residual solution in the reactor, take out the gold flakes in the reactor in step (1), wash them with deionized water for 2 to 3 times, and after natural air drying, a layer of hafnium dioxide coating can be seen on the surface of the gold flakes.
[0107] Figure 7 The scanning electron microscope images in (a) and (b) show the hafnium dioxide nanofilm; Figure 7Figures (c) to (d) are scanning electron microscope photos of hafnium dioxide at different magnifications. The morphology shows that these hafnium dioxides are relatively self-shaped short rods with a particle size of 200 nanometers to 1500 nanometers.
[0108] Fig. 9 The laser Raman spectroscopy analysis in the experiment showed that the laser Raman peak of the nanocrystals synthesized at 400°C was obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm -1 、258cm -1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1 , indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0109] Fig.10 The XRD powder diffraction analysis in the results shows that the hafnium dioxide crystals are monoclinic and have developed multiple crystal planes such as (111), (200), (020), (022), and (300).
[0110] Example 7
[0111] The method for synthesizing monoclinic hafnium dioxide nanorods provided in this embodiment comprises the following steps:
[0112] (1) The filtrate obtained in step (2) of Example 1 was diluted with deionized water to obtain a 0.02 mol / L reaction solution. 5 mL of the prepared reaction solution was placed in a gold tube with a diameter of 4.5 mm and then welded and sealed. The gold tube was then placed in a high-temperature and high-pressure reactor. The high-temperature and high-pressure reactor was connected to a high-precision ultra-high pressure pressure gauge, a ventilation pipe and a stop valve. The high-temperature and high-pressure reactor had a stainless steel or Hastelloy metal shell. After the reactor was tightened, argon was injected into the reactor through the ventilation pipe to a pressure of 80 MPa. The stop valve was closed to stop the gas injection. The reactor was heated by a heating furnace and the reaction temperature was set to 500° C. After the temperature rose to 500° C., the stop valve was opened and argon was continuously injected to a pressure of 100 MPa. The reaction time was maintained for 12 hours. After the reaction was completed, ice water was used to pour the reactor to quickly cool it to room temperature.
[0113] (2) Open the reactor in step (1), take out the gold tube in step (1), break it open, wash the inner wall of the gold tube with deionized water, collect the washed fluid to obtain nano hafnium dioxide turbid liquid, place the obtained turbid liquid in a centrifuge for centrifugation, take out the lower precipitate after centrifugation and rinse it with deionized water for 2 to 3 times, and finally air-dry the precipitate to obtain hafnium dioxide nanorods.
[0114] Figure 8 Figures (a) to (d) show the morphology and particle size of hafnium dioxide nanorods at different magnifications, with particle sizes ranging from 200 nanometers to 1000 nanometers.
[0115] Fig. 9 The laser Raman spectroscopy analysis in the experiment showed that the laser Raman peak of the nanocrystals synthesized at 500°C was obvious, with 10 Raman scattering peaks similar to those of standard hafnium dioxide powder, namely 115 cm -1 、138cm -1 、151cm -1 、258cm -1 、385cm -1 , 500cm -1 、582cm -1 、641cm -1 and 672cm -1 , indicating that the short rod-shaped nanocrystals are hafnium dioxide crystals.
[0116] The above embodiments are only used to illustrate the present invention, and the protection scope of the present invention is not limited to the above embodiments. A person skilled in the art can achieve the purpose of the present invention based on the above disclosure of the present invention, and any improvement and deformation based on the concept of the present invention shall fall within the protection scope of the present invention, and the specific protection scope shall be subject to the claims.
Claims
1. A method for synthesizing monoclinic hafnium dioxide nanorods, characterized in that: The following steps are involved: (1) Using hafnium dioxide and potassium bifluoride powder as initial raw materials, the two raw materials are placed in a container and covered, and the container is heated to a temperature of 350 to 400° C. for a heating time of 0.25 to 1 hour to allow the solid powder to undergo a sufficient melting reaction, and then cooled after the reaction, a dilute hydrofluoric acid solution is added to the container, and the container is heated to boiling again, and the container is continuously stirred to completely dissolve the solid in the container, and the heating is stopped; (2) filtering the solution in the container while hot and collecting the filtrate; (3) diluting the filtrate obtained in step (2) with deionized water to obtain a dilute solution, placing the dilute solution in a hydrothermal reaction container, sealing the hydrothermal reaction container, heating the hydrothermal reaction container, adjusting the temperature in the hydrothermal reaction container to 150-500° C., adjusting the pressure in the hydrothermal reaction container to 10-100 MPa by injecting inert gas into the hydrothermal reaction container, reacting for 10-15 hours, and rapidly cooling to room temperature after the reaction; (4) Opening the hydrothermal reaction vessel, and obtaining monoclinic hafnium dioxide nanorods through subsequent treatment.
2. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 1, characterized in that: The mass ratio of hafnium dioxide to potassium bifluoride in step (1) is 1:2-3; the volume percentage of the dilute hydrofluoric acid solution in step (1) is 3-8%, and the amount added is 40-60% of the total volume of the container; the container in step (1) is a crucible, and the crucible is a nickel-based alloy crucible or a precious metal crucible; and a Teflon stirring rod is used for stirring in step (1).
3. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 1, characterized in that: In step (2), a silver evaporating dish or an evaporating dish with a Teflon lining is used to collect the filtrate.
4. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 1, characterized in that: The molar concentration of the dilute solution in step (3) is 0.01-0.02 mol / L; the inert gas in step (3) is argon or helium.
5. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 1, characterized in that: In step (3), the dilute solution is directly added to the hydrothermal reaction vessel, and the volume of the dilute solution accounts for 30-80% of the total volume of the hydrothermal reaction vessel; the hydrothermal reaction vessel is a hydrothermal reaction kettle, and the hydrothermal reaction kettle is a sealed high-temperature and high-pressure reaction kettle, and the high-temperature and high-pressure reaction kettle is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reaction kettle has a metal shell, and the metal shell is provided with a strong acid and strong alkali resistant lining, and the strong acid and strong alkali resistant lining is polytetrafluoroethylene, polyphenyl ester, polyimide plastic, or the strong acid and strong alkali resistant lining is silver, gold or platinum inert metal, or the strong acid and strong alkali resistant lining is gold palladium, silver palladium alloy.
6. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 5, characterized in that: In step (4), the hydrothermal reaction vessel is opened, and the monoclinic hafnium dioxide nanorods are obtained through subsequent treatment, which includes: opening the hydrothermal reaction vessel, recovering the residual solution in the hydrothermal reaction vessel, washing the inner wall of the hydrothermal reaction vessel with deionized water, collecting the washed fluid to obtain a nano-hafnium dioxide turbid solution, centrifuging the obtained turbid solution, removing a lower layer of precipitate, and washing and drying the lower layer of precipitate to obtain monoclinic hafnium dioxide nanorods with uniform particle size.
7. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 5, characterized in that: In step (3), a sample collection sheet is provided at the bottom of the hydrothermal reaction container, and the sample collection sheet is a sample collection sheet made of plastic or inert metal. In step (4), the hydrothermal reaction container is opened, and the monoclinic hafnium dioxide nanorods are obtained through subsequent treatment, including: opening the hydrothermal reaction container, recovering the residual solution in the hydrothermal reaction container, taking out the sample collection sheet, washing and drying, and obtaining hafnium dioxide nanorods with uniform particle size on the surface of the sample collection sheet.
8. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 1, characterized in that: In step (3), the dilute solution is first added to a precious metal vessel, and then the precious metal vessel is placed in a hydrothermal reaction vessel, wherein the precious metal is silver, gold or platinum; or the precious metal is gold-palladium or silver-palladium alloy; the high-temperature and high-pressure reactor is connected to a high-precision ultra-high-pressure pressure gauge, a ventilation pipe and a stop valve, and the high-temperature and high-pressure reactor has a metal shell.
9. The method for synthesizing monoclinic hafnium dioxide nanorods according to claim 8, characterized in that: In step (4), the hydrothermal reaction vessel is opened, and the monoclinic hafnium dioxide nanorods are obtained through subsequent treatment, which includes: opening the hydrothermal reactor, taking out the precious metal container, recovering the residual solution in the precious metal container, washing the inner wall of the precious metal container with deionized water, collecting the washed fluid to obtain nano hafnium dioxide turbid solution, centrifuging the obtained turbid solution, removing the lower precipitate, and washing and drying the lower precipitate to obtain monoclinic hafnium dioxide nanorods with uniform particle size.
10. Use of the monoclinic hafnium dioxide nanorods synthesized by the method according to any one of claims 1 to 9 in coating on plastic or metal surfaces.
Citation Information
Patent Citations
Preparation method of monoclinic zirconia nano product
CN110240195A